Emotional intelligence and job satisfaction among employees at University College Sabah Foundation (UCSF) / Maslinda Abdul Ghanie - Abdul Ghanie, Maslinda (2014)
The competition in today's business environments requires organizations to hire employees with high Emotional Intelligence (EI). Even though Intellectual Intelligence (IQ) may be important for all employees, it does not always guarantee that they can certainly be good employees. Emotional intelligence is an important consideration in human resources planning, performance of employees' job profiling, recruitment interviewing and selection, management development, customer relations and customer service, and others. The main purpose of this study to examine the level of emotional intelligence of employees at University College Sabah Foundation. The study also sought to investigate how emotional intelligence is correlated with job satisfaction among employees at University College Sabah Foundation. Another purpose of this study is to determine whether there is any difference of emotional intelligence level between genders. Hence, this study was conducted among all the employees in the organization, which consist of 120 employees. Quantitative methodology were utilized in this study. The data collection involved questionnaires which were administered to all employees in the organization. However, only 113 questionnaire were managed to be collected. In this research, Spearman's rank-order correlation and Mann-Whitney test were used as the data are not normal. Frequency and Descriptive Analysis were also used to analyze respondents' background and to measure the level of emotional intelligence and job satisfaction. The result of this study discovered that the majority of the students possessed average level of Emotional Intelligence as well as having average satisfaction towards their job. The study also revealed that emotional intelligence is moderately correlated with job satisfaction. However, the result of the study shows that gender does not have significant correlation with one's emotional intelligence. Based on these results, it is highly recommended for this organization to implement ongoing effort to develop more emotional intelligence based trainings as it can be learned. Additionally, the employees will have better satisfaction towards their job once they keep on improving their level of emotional intelligence; which lead to better performance and better job satisfaction.